Repeatability of vertical ground reaction force estimation during running on the athletics track on 3 different days - Scheltinga, B. L.; Buurke, J. H.; Kok, J. N.; Reenalda, J. (Journal of Applied Biomechanics, 2025)
To increase understanding in development of running injuries, the biomechanical load over time should be studied. Ground reaction force (GRF) is an important parameter for biomechanical analyses and is typically measured in a controlled lab environment. GRF can be estimated outdoors, however, the repeatability of this estimation is unknown. Repeatability is a crucial aspect if a measurement is repeated over prolonged periods of time. This study investigates the repeatability of a GRF estimation algorithm using inertial measurement units during outdoor running. Twelve well-trained participants completed 3 running sessions on different days, on an athletics track, instrumented with inertial measurement units on the lower legs and pelvis. Vertical accelerations were used to estimate the GRF. The goal was to assess the algorithm`s repeatability across 3 sessions in a real-world setting, aiming to bridge the gap between laboratory and outdoor measurements. Results showed a good level of repeatability, with an intraclass correlation coefficient (2, k) of .86 for peak GRF, root mean square error of .08 times body weight (3.5%) and Pearson correlation coefficients exceeding .99 between the days. This is the first study looking into the day-to-day repeatability of the estimation of GRF, showing the potential to use this algorithm daily.